Investigating the moderating role of Export PromotionProgrammes using evidence from North-Africa - Yacine Haddoud, Mohamed (2017)
Purpose– Based on an institutional approach to explaining firms’ internationalisation, this paper aims to empirically investigate the role of Export Promotion Programmes (EPPs) in moderating the influence of export barriers perceptions on small and medium enterprises’ (SMEs) propensity to export. Design/methodology/approach– The study uses evidence from Algeria, the largest North-African country. The data were collected using an online questionnaire, targeting SMEs operating in the manufacturing sector. The study considers the influence of procedural, informational, environmental and functional barriers on export propensity, to uncover the moderating role of trade missions, trade shows and export seminars and workshops on such relationships. To examine these links, five main hypotheses are proposed and tested through a non-linear partial least squares structural equation modelling on a sample of 128 Algerian SMEs. Findings– Theresults show that while internal barriers decrease firms’ export propensity, EPPs including trade fairs and showsmayindependentlypose eitherapositive ornegativeinfluenceonsuch relationships. Research limitations/implications– The study confirms the applicability of the institutional perspective to explaining firms’ internationalisation. More importantly, the present study highlights the role of EPPs in moderating the influence of export barriers perceptions on SMEs’ international market entry, a role neglected by the extant empirical literature. Practical implications– The current findings hold important implications to export promotion organisations operating in African countries. Notably, the results reveal that some programmes could have a negative influence if they arenot delivered appropriately. Originality/value– This study offers a rare focus on the moderating role of EPPs in the relationship between export barriers andexport propensity, within thesetting of a North-African country.